2015
DOI: 10.1080/0965254x.2015.1035036
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of competitive advantage: towards a contingency theory of entrepreneurial marketing

Abstract: Entrepreneurial marketing (EM), born out of the practice of firms operating in conditions of uncertainty, is emerging as a powerful alternative to cope with the decreasing effectiveness associated with traditional marketing. In this article, the authors provide their collective position regarding the field of EM. A brief history and conceptual background of EM is presented and the contextual differences that have shaped its evolution are considered. Distinctions between traditional and EM are derived based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 57 publications
2
109
1
9
Order By: Relevance
“…In light of the result of this study, it can be concluded that social enterprises have to strengthen their opportunity-seeking abilities (Gilmore, 2011;Morris et al, 2002;Whalen et al, 2016) in order to perform better in the market. They also have to employ more creative (Kotler & Keller, 2012) and innovative approaches (Olofsson, 2015;Rydback & Chen, 2010;Shaw, 2004), i.e., not counting on traditional marketing approaches that much in facing the market environment and competition since change is a necessity for competing triumphantly (Asiedu, Byrne, & Corena, 2011;Sigasa, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In light of the result of this study, it can be concluded that social enterprises have to strengthen their opportunity-seeking abilities (Gilmore, 2011;Morris et al, 2002;Whalen et al, 2016) in order to perform better in the market. They also have to employ more creative (Kotler & Keller, 2012) and innovative approaches (Olofsson, 2015;Rydback & Chen, 2010;Shaw, 2004), i.e., not counting on traditional marketing approaches that much in facing the market environment and competition since change is a necessity for competing triumphantly (Asiedu, Byrne, & Corena, 2011;Sigasa, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…EM is a combination of innovative, proactive, and risk-taking activities that create, communicate, and deliver value to and by customers, entrepreneurs, marketers, their partners, and society at large (Whalen et al, 2016) Table 1 Entrepreneurial marketing processes compared to traditional marketing concepts (Stokes, 2000) Marketing…”
Section: Entrepreneurial Marketingmentioning
confidence: 99%
“…Crick (2018a) explored the: facets, antecedents, and consequences of coopetition, using three dimensions of entrepreneurial marketing, namely: a proactive orientation, resource leveraging behaviours, and innovation-focused behaviours. While Crick (2018a) highlighted that it would have been interesting to apply all seven dimensions of entrepreneurial marketing to coopetition activities (Morris et al, 2002;Whalen et al, 2016), the three that were selected explained: how coopetition can be managed (the facets of coopetition), the factors that motivate entrepreneurs to cooperate with their competitors (the antecedents of coopetition), and the performance outcomes that such strategies might yield (the consequences of coopetition). Crick (2018a) selected these three dimensions of entrepreneurial marketing, as they were conceptually-related to the coopetition literature (Bjerke and Hultman, 2002;Hills et al, 2008; (Alves and Meneses, 2015;Crick and Crick, 2016;Crick, 2018a;Daidj and Egert, 2018), but more research is needed to integrate these two strands of literature.…”
Section: Facets Antecedents and Consequences Of Coopetitionmentioning
confidence: 99%
“…As coopetition activities have scarcely been incorporated into the entrepreneurial marketing literature (Alves and Meneses, 2015;Crick and Crick, 2016;Crick, 2018a;Daidj and Egert, 2018), it is proposed that scholars, exploring this field, can use their expertise to fill such research gaps. Further, the marketing/entrepreneurship interface is far from being a saturated research domain (i.e., there are plenty of issues that need to be addressed) (O'Donnell Gilmore, 2011;Mort et al, 2012;Gross et al, 2014;Miles et al, 2015; O'Cass and Morrish, 2016;Whalen et al, 2016). Entrepreneurial marketing scholars should investigate coopetition activities, as well as their: antecedents, consequences, and boundaries to study how collaborating with competitors helps entrepreneurs to overcome certain resource-disadvantages by accessing new: resources, capabilities, and opportunities from their competitors (as per Bengtsson and Johansson, 2014;Granata et al, 2018;Mathias et al, 2018).…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation